DEVELOPING EMOTIONAL INTELLIGENCE: EMOTIONALLY AWARE TEACHING METHODS - Elamanova Dildora (Innovate Conferences, 2025)
This article analyzes the pedagogical foundations of the formation of emotional intelligence in students, in particular, the role of emotionally conscious teaching methods. The author substantiates the importance of teacher strategies in the development of emotional stability, self-awareness, understanding of others, and social skills. The article is enriched with methodological approaches and practical recommendations.
Keywords: emotional intelligence, emotional awareness, emotional literacy, conscious teaching, socio-emotional learning, reflection.